2010
DOI: 10.1029/2009wr007875
|View full text |Cite
|
Sign up to set email alerts
|

Plot‐scale effects on runoff and erosion along a slope degradation gradient

Abstract: Citation for published item:worenoEde ls rersD wF nd xioluD tFwF nd werinoEwrt¡ %nD vF nd iloxD fFF @PHIHA 9lotEsle e'ets on runo' nd erosion long slope degrdtion grdientF9D ter resoures reserhFD RT @RAF HRSHQF Further information on publisher's website: httpsXGGdoiForgGIHFIHPWGPHHWHHUVUS Publisher's copyright statement:worenoEde ls rersD wFD xioluD tFwFD werinoEwrt¡ %nD vF iloxD fFF @PHIHAF lotEsle e'ets on runo' nd erosion long slope degrdtion grdientF ter esoures eserh RT@RAX HRSHQD IHFIHPWGPHHWHHUVUS @hysA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 58 publications
5
104
2
2
Order By: Relevance
“…Early studies showed that general slope parameters influencing runoff generation and soil erosion are slope gradient, length, and shape (Wischmeier & Smith 1978). The effects of length (Kinnell 2000, 2007, Rejman & Brodowski 2005, Bagarello & Ferro 2010 and slope gradient (Bracken & Kirkby 2005, Assouline & Ben-Hur 2006, Moreno de las Heras et al 2010) on soil loss and runoff were studied extensively, with the general conclusions that eroded materials and runoff increase with higher slope steepness (Young & Mutchler 1969a, Wischmeier & Smith 1978, Liu et al 1994, Gabriels 1999, Chaplot & Le Bissonnais 2003. Moreover, a clear reduction in runoff for each unit of slope length was observed as slope length increased (Gascuel Odoux et al 1996, Aryal et al 2003, Parsons et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies showed that general slope parameters influencing runoff generation and soil erosion are slope gradient, length, and shape (Wischmeier & Smith 1978). The effects of length (Kinnell 2000, 2007, Rejman & Brodowski 2005, Bagarello & Ferro 2010 and slope gradient (Bracken & Kirkby 2005, Assouline & Ben-Hur 2006, Moreno de las Heras et al 2010) on soil loss and runoff were studied extensively, with the general conclusions that eroded materials and runoff increase with higher slope steepness (Young & Mutchler 1969a, Wischmeier & Smith 1978, Liu et al 1994, Gabriels 1999, Chaplot & Le Bissonnais 2003. Moreover, a clear reduction in runoff for each unit of slope length was observed as slope length increased (Gascuel Odoux et al 1996, Aryal et al 2003, Parsons et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…De cualquier modo, la variación de la escorrentía con respecto al tamaño de parcela se hace prácticamente nula a partir de los 12 m de longitud de parcela. En consecuencia, de acuerdo con Moreno de las Heras et al (2010), podríamos tener en este estudio dos grupos de uso de suelo según su cobertura: los más protegidos serian Pinus, pastizal y matorral y los de menor cobertura almendro, olivar y suelo abandonado. Las tasas de tolerancia a la pérdida de suelo pueden diferir según la cubierta vegetal, clima, topografía, y diversas características del suelo.…”
Section: Resultsunclassified
“…For example, field observations in the Negev Highlands showed that frequency and magnitude of the specific runoff yield decreased with increasing area as a result of flow discontinuity and deposition processes along the hillslope (Yair and Raz-Yassif, 2004). Moreno-de las Heras et al (2010) observed that unit area sediment yield declined with increasing plot length for the undisturbed and moderately disturbed sites, but it actually increased for the highly disturbed sites, which was especially clear under highintensity rainfall conditions in a Mediterranean dry environment. Therefore, the plot-scale effects of runoff and erosion were dependent on the extent of degradation.…”
Section: Discussion Of the Proposed Approachmentioning
confidence: 99%
“…Liu et al (2012) found that soil loss rates decreased with the plot area in Group 2 and Group 3 plots with longer restoration time, but they increased over an area threshold in Group 1 plot located at the early stage of revegetation, which was not totally consistent with the USLE/RUSLE model. One of the main reasons for the complex plot-scale effects of soil loss is the connectivity and distribution of runoff and sediment source and sink areas on hillslope (Yair and Raz-Yassif, 2004;Parsons et al, 2006;Moreno-de las Heras et al, 2010). Therefore, not only plot length, but the other factors such as rainfall regime, soil property, and vegetation cover contribute to scale variations of runoff and soil loss.…”
Section: Discussion Of the Proposed Approachmentioning
confidence: 99%